Reimplantasi Gigi Incisivus Dua Atas dengan Kista Radikular - R.Wasis Sumartono; Tince Armiati Jovina (Faculty of Dentistry, Universitas Indonesia, 2015)
A reimplantation case of maxillary second incisive with periapical (radicular) cyst is reported. A 37 years old female who suffered periapical cyst on her maxillary second incisive requested conventional endodontic treatment in order to avoid tooth extraction. The tooth was treated with a conventional root canal treatment at the first visit. After the first treatment, the patient suffered a post endodontic treatment pain but was afraid to be operated with apex resection. On the second visit, the maxillary second incisive was extracted. On the third visit the patient requested periapical cyst removal after she received advices from her older sister (who was a medical doctor) about the important of removing cyst capsule in order to avoid cyst recurrency. The patient also requested her tooth reimplantation. Following her request, on her extracted maxillary second incisive, root canal filling and apex resection were done out side her mouth, followed by periapical curettage in the maxillary second incisive region. Then reimplantion was finally performed. Seven months later, the patient told that since her maxillary second incisive apex resection and reimplantation, she never suffered from any pain or swelling. Pain on the tooth percussion and palpation were negative. Tooth mobility was on level 2. There was no sign that periapical radiolucency was growing wider, eventhough it was not getting smaller at that moment. We classified the result of our treatment as "not fail" since we still need a longer time ensure whether or not the result will be able to be classified as "successful". Eventhough radiographic healing was still "uncertain", there was a hope that the patient will gain a "complete healing" after 2 years.